WAYS OF PROVIDING EDUCATION OF A SPECIAL CHILD IN CONDITIONS OF INCLUSION - Serhii I. Netosov; Valеriia V. Liashenko (Alfred Nobel University Publisher, 2019)
The Ukrainian school today is undergoing fundamental changes, and inclusive education is one of the innovative directions of their implementation. The issues of theoretical and practical training of specialists, their mastery of the methodological and didactic tools for providing inclusive education are being actively investigated in the work of specialists, and the process of intensive and productive formation of the regulatory framework of the organization of inclusive education is underway. Inclusion is a process that requires the involvement of significant resources and major changes in the organization of training and education of special children. It is the system of effective functioning of the educational team in an inclusive education that the presented article is dedicated to. The aim of the work is to analyze and summarize the experience of working in an inclusive class with a special student, identifying ways of socializing a student with special educational needs. The article explored the course of social and pedagogical support of a particular child, the work of teachers, the relationship of the student with a class, the position of parents of a schoolgirl who was diagnosed with an autism spectrum disorder, Asperger syndrome. It was determined that one of the determining factors in creating a favorable microclimate for a child with special educational needs is not only the presence of defectologists, but also the readiness for cooperation of the family, teachers, the position of the school administration, cooperation with the inclusive resource center. On the basis of practical experience and theoretical generalizations, the ways of ensuring the socialization of that particular child in terms of inclusive education are formulated: 1) the need for the earliest diagnosis of psychophysical problems of the child; 2) parents' active position as members of the teaching team; 3) providing theoretical and methodological training of teachers to work with special children; 4) the creation and implementation of a system of cooperation and mutual understanding of the family with the teachers of a special child; 5) establishment of close personal and professional contact of the assistant of the special child with the teachers of the school; 6) one of the main areas of work with the school community should be the formation of tolerance, the recognition of the characteristics of each individual, the education of mercy and humanism in the school environment. The readiness of teachers, families and society to implement the education of children with special educational needs is the strategic objective of the socialization of each particular child and the country's democratic development.